Practice and Reflection on Rammed Earth Architecture: The Case Study of Tiles Hill–Xiangshan Campus Reception Centre in China - Lichao Chen; Zhiyu Lan; Chaochao Wei; Dan Ouyang; Boren Shi; Peiyin Chen; Mingzhe Wang; Tianyi Xie (Buildings)
This article documents the rammed earth construction practices undertaken at the “Tiles Hill–Xiangshan Campus Reception Centre” project. Traditional rammed earth craftsmanship is a sustainable construction method, with its core rooted in the precise material ratios and building techniques. This project aimed to explore the revival of this nearly forgotten vernacular construction method by integrating modern building technologies, all while adhering to the principle of avoiding any stabilizer additives. The project utilized a total of 2200 cubic meters of rammed earth to construct 16 walls, predominantly oriented north-south, with heights ranging from 3.6 m to 9.6 m and a thickness of 0.6 m. Before the formal commencement of the project, the team conducted experiments in the laboratory, constructing test walls to determine the optimal template fabrication and installation system compatible with modern rammed earth techniques. During the construction process, the team refined the rammed earth techniques, addressing challenges such as wall tilting, horizontal cracking caused by material settlement, and the flexible connection between the earthen walls and the primary structural framework through rational structural node design. The walls also passed compressive strength tests. Furthermore, advancements in the construction process allowed for the recycling and reuse of excavated soil. The article emphasizes that the sustainability of rammed earth techniques extends beyond material reuse to encompass the material’s inherent environmental friendliness and nondestructive nature. It argues that, provided there is a thorough understanding of the material properties of soil and reasonable structural and node design, coupled with the addition of necessary structural measures, it is entirely feasible to achieve ecological sustainability in rammed earth construction without the use of stabilizing additives.